2019
DOI: 10.3390/ijms20051204
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Changes in Medicago truncatula and Lotus japonicus Root Nodules during Drought Stress

Abstract: Drought is one of the major environmental factors limiting biomass and seed yield production in agriculture. In this research, we focused on plants from the Fabaceae family, which has a unique ability for the establishment of symbiosis with nitrogen-fixing bacteria, and are relatively susceptible to water limitation. We have presented the changes in nitrogenase activity and global gene expression occurring in Medicago truncatula and Lotus japonicus root nodules during water deficit. Our results proved a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 118 publications
1
10
0
1
Order By: Relevance
“…Other studies have indicated that drought induces similar changes in both determinate-and indeterminate-type nodules (Gil-Quintana et al, 2015). The differences in gene expression were attributed to different nodule types (Sańko-Sawczenko et al, 2019). Dehydration of the cell membrane causes damage to the lipid bilayer, and this can jeopardize the bacterial survival during drought (Bushby and Marshall, 1977).…”
Section: Droughtmentioning
confidence: 98%
“…Other studies have indicated that drought induces similar changes in both determinate-and indeterminate-type nodules (Gil-Quintana et al, 2015). The differences in gene expression were attributed to different nodule types (Sańko-Sawczenko et al, 2019). Dehydration of the cell membrane causes damage to the lipid bilayer, and this can jeopardize the bacterial survival during drought (Bushby and Marshall, 1977).…”
Section: Droughtmentioning
confidence: 98%
“…The expression of SUS1 genes (gene IDs MS.gene030241 and Medtr4g124660 for Ms and Mt, respectively) was quantified by qRT-PCR using the F-box/ankyrin repeat SKIP35-like proteinencoding gene as a reference (gene IDs MS.gene95033 and Medtr4g134960 for Ms and Mt, respectively; Sañko-Sawczenko et al, 2019). cDNA synthesis, qRT-PCR, DNase I treatment, and data analysis were conducted as previously described (Le et al, 2012).…”
Section: Phylogenetic and Expression Analyses Of The Sus Familymentioning
confidence: 99%
“…(GO) enrichment analysis was carried out for root and shoot DEGs in order to determine the most represented GO terms for molecular function and biological processes (Figure 1). GO enrichment analysis has recently been used in several analyses of L. japonicus transcriptomes [35][36][37]. The most over-represented GO terms in roots were related to metabolism (catalytic activity, biosynthetic process), probably as a consequence of the different nitrogen regimes of Nod and NN plants.…”
Section: Transcriptomic Analysis Of Lotus Japonicus Symbiosismentioning
confidence: 99%